Art and Cultural Participation and Life Satisfaction in Adults: The Role of Physical Health, Mental Health, and Interpersonal Relationships - Lee, Chia-Wen; Lin, Li-Ching; Hung, Huang-Chia (Frontiers in Public Health, 2021)
Many different forms of art and cultural participation, for example, visiting museums and galleries, have received increasing attention as an important new focus for public health. While a growing body of evidence suggests that art and cultural participation enhance human health and well-being in the West, the research is just in the infancy in the East. The purpose of this study was to explore the effects of art and cultural participation of museums and galleries on life satisfaction intervened and controlled by physical and mental health and interpersonal relationships and individual's background. This study adopted large-sample data from the seventh period of the Taiwan Social Change Survey. The sample population comprised 2,034 adult participants, involving 1,042 males and 992 females. The average age of the respondents was 47.67 ± 17.48 years. The results showed that individuals aged 30–64 years with an average monthly income between NT$20,000–NT$40,000 had a higher frequency of art and cultural participation of museums and galleries. Women under 29 years reported better life satisfaction. Individuals with a higher frequency of art and cultural participation of museums and galleries affected life satisfaction not only directly but also indirectly through interpersonal relationships, particularly among women and the elderly. Individuals who visited museums and galleries more frequently had greater life satisfaction and higher frequency of interpersonal contact. This was particularly evident in older females. Art and cultural participation of museums and galleries directly affected individual's life satisfaction and indirectly affected it via interpersonal relationships after controlling for gender, age, and monthly income. These findings indicate that visiting museums and galleries can enhance the frequency of interpersonal interactions and life satisfaction.